Studi Eksplorasi Komunitas Pedesaan: Kehidupan Emosional Anak Hingga Lansia dalam Keluarga Multigenerasi - Andrika Telaumbanua; Irvan Sabelau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This research explores the emotional lives of individuals in multigenerational families in rural communities, focusing on children, adolescents and the elderly. In the context of a rural community that generally has a close-knit and interdependent family structure. This study aims to understand the emotional dynamics that occur between different generations and how this can affect individual well-being as well as relationships between family members. The research methods used included in-depth interviews, participatory observation, and thematic analysis of data collected from several villages representing the socio-economic diversity of the region. The results of this study show that emotional relationships in rural multigenerational families are often characterized by closeness and reciprocity, but also face challenges such as generational conflict and economic pressures. This study provides insights into how multigenerational family dynamics affect the well-being and emotional lives of family members.